Developing mathematical literacy test with context of Bugis-Makassar local wisdom for junior high school students - Nursakiah Nursakiah; Fathrul Arriah; Surya Dharma (Universitas Hamzanwadi, 2022)
Various studies on the development of mathematical literacy tests have not shown any research that focuses on developing mathematical literacy tests using the context of Bugis-Makassar local wisdom with Classical Test Theory (CTT). Thus, this study aimed to produce mathematical literacy tests using the context of Bugis-Makassar local wisdom based on CTT for junior high school students through development research using ADDIE design. The development of the test integrates mathematical literacy and local wisdom elements of Bugis-Makassar. There were 15 multiple-choice items developed and tested on 33 males and 68 females at seventh-grade junior high school students. The trial involved two schools in Makassar City using a convenience sampling technique. The test kit was validated by three mathematicians and produced an Aiken index score in the range of 0.67 to 0.89. The empirical data from the trial results were analyzed using CTT assisted by ITEMAN 4.3 software. The test analysis showed an average category for reliability test scores. As many as 47% of the items were in the medium category, and the rest were in the fair category. Meanwhile, 93% of the items have a good discriminatory ability, and 67% have distractors that were not functioning properly, then the tests items must be revised.